2016
DOI: 10.3390/su8060566
|View full text |Cite
|
Sign up to set email alerts
|

The Livelihood Vulnerability of Rural Households in Earthquake-Stricken Areas—A Case Study of Ning’er, Yunnan Province

Abstract: Earthquakes happen suddenly and are immensely destructive. They not only destroy entire societal production and infrastructure systems but also seriously interfere with daily life and reduce opportunities to earn income in earthquake-affected areas. In this paper, using the Ning'er Ms 6.4 earthquake in 2007 as an example, we analyzed the livelihood vulnerability of rural households in Ning'er County, Yunnan, based on data from questionnaires and on-site interviews. The results showed that on the whole, local r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Previous studies estimating the effects of natural disasters have mainly focused on individual telecouplings separately while treating either socioeconomic (Blaikie et al 2014, Yang et al 2015, Wei et al 2016 or ecological effects (Garwood et al 1979, Zheng et al 2012 independently. Although these disparate research foci have generated useful insights into the effects of natural disasters, more comprehensive research is needed to integrate various aspects of natural disasters' influences into a systematic assessment of patterns, processes, simultaneous socioeconomic and environmental interactions, and implications for governance and policy across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies estimating the effects of natural disasters have mainly focused on individual telecouplings separately while treating either socioeconomic (Blaikie et al 2014, Yang et al 2015, Wei et al 2016 or ecological effects (Garwood et al 1979, Zheng et al 2012 independently. Although these disparate research foci have generated useful insights into the effects of natural disasters, more comprehensive research is needed to integrate various aspects of natural disasters' influences into a systematic assessment of patterns, processes, simultaneous socioeconomic and environmental interactions, and implications for governance and policy across the world.…”
Section: Introductionmentioning
confidence: 99%
“…It does not depend so much on the spatial distribution of hazards, but on the characteristics of urban fabric [3] and sometimes on the social-economic state of households [15] sustainable livability, which diminishes vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Urban seismic vulnerability actually describes the degree to which physical assets and social-economic systems are susceptible or resilient to the impact of earthquakes [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…The effective response rate was up to 97.2%. The sample number is sufficient to meet the needs of a 95% confidence level and 0.05 sampling error [26]. Table 4 lists the basic characteristics of the questionnaire respondents: 69.75% male and 30.25% female respondents because most headers of rural families are male in China.…”
Section: Questionnaire Investigationmentioning
confidence: 99%
“…The results showed that livelihoods capitals have an increasing trend in all five dimensions, including human, physical, natural, financial and social capitals, after recovering from the earthquake. Wei et al [26] estimated the livelihood risk of rural households based on a sustainable livelihood framework in Ning'er earthquake-hit areas, Yunnan Province. The results showed that the vulnerable livelihoods of local households had low capacity to deal with the effects of the earthquake.…”
mentioning
confidence: 99%